SARS-CoV-2 multi-epitope subunit vaccine proof-of-concept derived from the in silico study with protein expression in E. coli BL21 - Muhayya, Syarifah Raisha; Agus Ariyanto, Ibnu; Widianingtyas, Silvia; Subiantistha, Tanaya; Bela, Budiman (Brawijaya University, 2024)
The protein subunit vaccine is the most considerably developed SARS-Cov-2 vaccine, according to the WHO vaccine tracker in 2023. The acceleration of vaccine development in 2 years of eradicating the COVID-19 pandemic is attainable due to the role of bioinformatics. The objective of this paper is to evaluate strategies for developing multi-epitope SARS-Cov-2 recombinant vaccines with high protein expression in silico. The study was conducted by analyzing SARS-Cov-2 epitopes using immunoinformatics tools provided by IEDB, codon optimization, rare codon analysis, plasmid design, and ribosomal binding site (RBS) analysis were analyzed using RNA structure 6.4, gene cloning by E. coli DH5α and protein expression by E. coli BL21. Each epitope peptide candidate was linked to a flexible linker sequence (GGGGS). GelAnalyzer 19.1 was utilized to determine the protein band of SDS-PAGE. The immunoinformatics study obtained multi-epitope of the recombinant SARS-COV-2 vaccine with a total of 7 epitopes for HLA-I allele candidates and 4 for HLA-II. It is demonstrated that the candidate vaccine protein was successfully cloned in E. coli DH5α and expressed in E. coli BL21.